Six new alien phytophagous insect species recorded in Slovenia in 2011 - Seljak, Gabrijel (Acta entomologica slovenica (Ljubljana), 2012)
Six alien phytophagous insects found in 2011 in Slovenia for the first time are presented: Dichromothrips corbetti (Thysanoptera, Thripidae), Aleuroclava aucubae and Pealius azaleae (Hemiptera, Aleyrodidae), Ceroplastes ceriferus (Hemiptera, Coccidae), Cydalima perspectalis (Lepidoptera, Crambidae) and Aproceros leucopoda (Hymenoptera, Argidae). Pathways of their introduction and spread as well as their potential phytosanitary and environmental impacts are briefly discussed.
Keywords: alien insects; Slovenia; Slovenija; tujerodne žuželke